2022
DOI: 10.1186/s12977-022-00591-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunoescape of HIV-1 in Env-EL9 CD8 + T cell response restricted by HLA-B*14:02 in a Non progressor who lost twenty-seven years of HIV-1 control

Abstract: Background Long-Term Non-Progressors (LTNPs) are untreated Human Immunodeficiency virus type 1 (HIV-1) infected individuals able to control disease progression for prolonged periods. However, the LTNPs status is temporary, as viral load increases followed by decreases in CD4 + T-cell counts. Control of HIV-1 infection in LTNPs viremic controllers, have been associated with effective immunodominant HIV-1 Gag-CD8 + T-cell responses restricted by protective HLA-B alleles. Individuals carrying HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…A prophylactic vaccine strategy in NHPs targeting only three CD8 þ T-cell epitopes was sufficient to maintain viral control after SIV challenge and viral escape from these three epitopes occurred concomitantly with loss of control of viral replication [65]. Similarly, viral escape of a single epitope has also been associated with loss of long-term control in a person with HIV [66]. These data suggest that a few well targeted epitopes might be sufficient to induce viral control.…”
Section: Epitope Targetingmentioning
confidence: 85%
“…A prophylactic vaccine strategy in NHPs targeting only three CD8 þ T-cell epitopes was sufficient to maintain viral control after SIV challenge and viral escape from these three epitopes occurred concomitantly with loss of control of viral replication [65]. Similarly, viral escape of a single epitope has also been associated with loss of long-term control in a person with HIV [66]. These data suggest that a few well targeted epitopes might be sufficient to induce viral control.…”
Section: Epitope Targetingmentioning
confidence: 85%
“…Interestingly, long‐term nonprogression (LTNP) in HIV+ individuals has also been associated with the HLA‐B*14:02 allele. Specifically, LTNP is linked to an immunodominant response to the viral peptide Env‐EL9 that is presented by HLA‐B14*02 33 and is more protective than the response mediated by the presentation of Gag viral peptides by the HLA‐B*14:01 allele 34 . We hypothesize that HLA‐B*14:02 could have a similar role in SARS‐CoV‐2 infection and could be associated with a faster viral clearance through the presentation of a particular viral peptide that elicits a more effective response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the neutralizing activity of an antibody binding to the Env trimer, other immune recognition events are important for protection and impose selective pressure on the Env protein sequence. Protective CD8+ T-cell epitopes are well-established in the context of certain class I HLA alleles, but most of these epitopes are located in the Gag gene product; their importance is limited to human populations bearing the relevant HLA alleles, and they are subject to rapid selection of resistant mutations. An antibody epitope in the V2 domain of Env has been investigated for its potential importance in protection by ADCC, but numerous animal studies and human trials so far have not provided a robust confirmation. , In one of the few examples of association of disease with a CD4+ epitope, Ranasinghe et al reported the positive correlation of viral load with the CD4+ T-cell response to a C2 epitope (corresponding to cluster 3 above) . Mutation of nearby glycosylated residues has been shown to substantially modify presentation of gp120 and alter T-cell responses .…”
Section: Unstable and Metastable Viral Surface Proteinsmentioning
confidence: 99%